Resveratrol Inhibition of Renal Cancer Stem Cell Characteristics and Modulation of the Sonic Hedgehog Pathway. (10th June 2021) - Sun, Hongliang; Zhang, Taotao; Liu, Rui; Cao, Wanshuang; Zhang, Zhiqiang; Liu, Zhiqi; Qian, Weiwei; Wang, Dengdian; Yu, Dexin; Zhong, Caiyun
Abstract: Aims: Renal cell cancers typically exhibit high metastasis and recurrence, and this is thought to be due to renal cancer stem cells (CSCs). Meanwhile, aberrant activation of Sonic hedgehog (Shh) signaling is linked with CSCs. Resveratrol has direct or indirect impacts on the pathological activities of CSCs. However, the effects of resveratrol on renal CSCs remain to be elucidated. Methods: We cultured renal CSCs in serum-free medium. Western blotting was used to analyze the expression levels of related proteins. The mRNA changes were detected by qRT-PCR after resveratrol treatment. The CD133 + cells were quantified by flow cytometry analysis. Immunofluorescence staining images showed the changes in CD44 and Smoothened expression in the cell spheres. Results: Renal CSCs were enriched by tumorsphere formation assays of ACHN and 786-O cells. Resveratrol treatments markedly decreased the size and number of cell spheres and downregulated the expression of the Shh pathway-related proteins and CSCs markers. Moreover, we observed that resveratrol inhibited cell proliferation and induced cell apoptosis, while purmorphamine upregulated the Shh pathway and weakened the effects of resveratrol on renal CSCs. Conclusions: These results suggested that resveratrol is a potential novel therapeutic agent that targets inactivation of renal CSCs by affecting the function of the Shh pathway.